Deciding which is the best 1H NMR predictor for organic compounds using statistical tools - Mah, W.H. (Academie des sciences, 2022)
1H NMR chemical shifts for 30 organic compounds (396 data points) were predicted using four NMR predictor software and compared with the experimental data from SDBS. The NMR predictors involved were MestReNova, ChemDraw, NMRShiftDB and ACD Workbook Suite. Root mean square deviation (RMSD) and mean absolute percentage error (MAPE) were calculated from the data obtained. One-way analysis of variance (ANOVA), Tukey's honestly significant difference (HSD) and t -test were carried out to analyse the statistical significance of the differences between the predictors. The results from the statistical analysis were used to predict chemical shifts of three organic compounds. Â© 2022 Elsevier Masson SAS. All rights reserved.